Is bean really a women’s crop? Men and women’s participation in bean production in Uganda - Nakazi, Florence; Njuki, Jemimah; Ugen, Michael Adrogu; Aseete, Paul; Katungi, Enid M.; Birachi, Eliud Abucheli; Kabanyoro, Ruth; Mugagga, Isaac Joseph; Nanyonjo, Grace (Springer, 2017)
Background Common bean one of the grain legumes that was traditionally considered a subsistence crop and therefore a woman’s crop in Uganda was prioritized for commercialization. This has transformed the crop from being a subsistence crop (food security crop) to a commercial crop with more men engaged in its production. Little is known about the possibility of gender conflicts in production activities as the crop finds market.